2019
DOI: 10.1177/0146167219838551
|View full text |Cite
|
Sign up to set email alerts
|

Why Social Threat Motivates Malevolent Creativity

Abstract: History is rife with examples of the dark side of creativity—ingenious weapons, novel torture practices, and creative terrorist attacks—yet its psychological origins are sparsely addressed and poorly understood. Building on work showing that social threat induces focused thinking as well as aggressive cognitions and readiness to fight, we propose that threats lead to more malevolent creativity and less creativity in threat-irrelevant domains. Prisoner’s dilemma games were modified to evoke threat of exploitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 54 publications
1
51
0
3
Order By: Relevance
“…Despite those caveats, the present study is the first to consider how childhood neglect is related to malevolent creativity by highlighting the roles of the Dark Triad personality traits. Since most prior studies focus on the influence of social atmosphere and general personality on malevolent creativity (Clark and James, 1999;Lee and Dow, 2011;Baas et al, 2019), this study extends previous studies and broadens people's understanding of malevolent creativity to a certain degree. Our findings suggest that childhood experiences can be a predictor of malevolent creativity and that Dark Triad personality traits play an important role.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Despite those caveats, the present study is the first to consider how childhood neglect is related to malevolent creativity by highlighting the roles of the Dark Triad personality traits. Since most prior studies focus on the influence of social atmosphere and general personality on malevolent creativity (Clark and James, 1999;Lee and Dow, 2011;Baas et al, 2019), this study extends previous studies and broadens people's understanding of malevolent creativity to a certain degree. Our findings suggest that childhood experiences can be a predictor of malevolent creativity and that Dark Triad personality traits play an important role.…”
Section: Discussionsupporting
confidence: 64%
“…While many studies have explored the predictors of malevolent creativity from environmental and individual aspects (Clark and James, 1999;Lee and Dow, 2011;Harris et al, 2013;Baas et al, 2019), the current study was the first to examine whether childhood neglect was associated with malevolent creativity in the general population and to examine the mediating effect of the Dark Triad traits on this relationship. Three important results were obtained from this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MCT (Perchtold-Stefan et al, under review) consisted of four realistic, open-ended problems that depicted different sorts of unfair behavior from peers/associates, as it was shown that malevolent creativity is likely to occur in unfair and provocative contexts (e.g., Harris and Reiter-Palmon, 2015;Baas et al, 2019). In the money item of the MCT, participants face the following scenario: "Your neighbor asks you to help him with renovations in his flat and offers to pay you for your troubles.…”
Section: Malevolent Creativitymentioning
confidence: 99%
“…Baas с коллегами показали, что в ситуации социальной угрозы люди предлагали больше вредоносных идей, чтобы победить соперников в переговорах, особенно если у них была высокая мотивация познания. Таким образом, благодаря своей диспозиционной мотивации систематически обрабатывать релевантную информацию, эти люди были более мотивированы к защите и агрессии в ответ на социальные угрозы и в продуцировании идей, наносящих вред [14]. Это исследование касается социального взаимодействия в переговорах и было спроектировано таким образом, что задание изначально провоцировало проявление враждебности к соперникам.…”
unclassified